Research Resiliency through Lean Labs. (14th May 2020) - Dagdeviren, Canan; Durak, Tolga; Sadat, David
Abstract : Academic research groups, especially the ones directed by new junior faculty are under pressure to produce high‐quality work timely while constrained by limited budget, resources, and lab space. A well‐organized lab is crucial for a wide range of reasons, from keeping costs low, to protecting the health and safety of users. The focus herein is on developing lab‐level systems that create a lean and productive space in the context of academic cleanrooms. The efforts made at implementing the 5S organizational methodology to improve cleanroom functions, including regulatory compliance, organization, and resource stewardship, is described. The quantifiable result is that chemical consumption spending is reduced by 41%, between 2018 and 2019, whereas materials consumption spending is reduced by 52%. Meanwhile, there is a 116% increase in the number of fabricated devices, showing greater output using less resources. This management system also proved itself to be beneficial during emergency situations. The recent COVID‐19 pandemic is one such instance that showcased the ability to systematically ramp‐down operations within 15 min, taking a huge burden away from the research group, and thus allowing to focus on what is most important during this time of crisis: the health and safety of the group and community. Abstract : The lean lab framework is implemented to improve academic cleanroom laboratory functions, including regulatory compliance, organization, and resource stewardship, all while balancing cost and waste versus overall productivity. Aside from the obvious perks (i.e., lower cost, greater output), this management system proves itself to be beneficial during emergency situations such as the recent COVID‐19 pandemic.